Reading Memory and Identity in the Texts of Medieval European Holy Women
XXIV, 264 p.
Keywords: Examines a range of texts commemorating European holy women from the ninth through fifteenth centuries. Explores the relationship between memorial practices and identity formation. Draws upon much of the recent scholarly interest in the nature and uses of memory.